Analysis of Banking Profitability Influenced By Company Financial Factors on the Indonesia Stock Exchange 2016-2018 - Gartima Sitanggang; Eko Wahyu Nugrahadi; Muhammad Yusuf; Humisar Sihombing; Azizul Kholis (Britain International for Academic Research (BIAR-Publisher), 2022)
Analysis of banking profitability is very important to study because there are many factors that affect profitability, including exchange rates, and interest rates which have an impact on profitability. For this reason, this study will discuss the interrelationships of all variables that can influence it. Observations were made on banking companies on the Indonesia Stock Exchange in 2016-2018. The sample was selected by determining the criteria so that 27 companies were netted by purposive sampling. After downloading the data sourced from wwwIDXx.co.id. Multiple regression analysis shows the test results at a significance of 5%, namely the Capital Adequacy Ratio (CAR) and Non-Performing Loans can affect Profitability with projections on ROA. Thus it can be concluded that partially or simultaneously all variables have a significant effect on the profitability of the banking company. This result is understandable because these two variables in theory can strengthen the increase in profitability. However, this study has limitations only on testing two variables for that future research is advised to add other non-financial variables that are predicted to strengthen banking profitability.